Pain and Vertebral Dysfunction in Dry Immersion: A Model of Microgravity Simulation Different from Bed Rest Studies - L. Treffel; N. Massabuau; K. Zuj; M.-A. Custaud; G. Gauquelin-Koch; S. Blanc; C. Gharib; C. Millet (Pain Research and Management)
Background. Astronauts frequently experience back pain during and after spaceflight. The aim of this study was to utilize clinical methods to identify potential vertebral somatic dysfunction (VD) in subjects exposed to dry immersion (DI), a model of microgravity simulation. Method. The experiment was performed in a space research clinic, respecting all the ethical rules, with subjects completing three days of dry immersion (n=11). Assessments of VD, spine height, and back pain were made before and after simulated microgravity. Results. Back pain was present in DI with great global discomfort during the entire protocol. A low positive correlation was found (Pearson r=0.44; P<0.001) between VD before DI and pain developed in the DI experiment. Conclusions. There is a specific location of pain in both models of simulation. Our analysis leads to relativizing constraints on musculoskeletal system in function of simulation models. This study was the first to examine manual palpation of the spine in a space experience. Additionally, osteopathic view may be used to select those individuals who have less risk of developing back pain.